2006
DOI: 10.4028/www.scientific.net/msf.530-531.99
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition of Rare Earth Oxide Concentrates on Oxidation Resistance of AISI 304L

Abstract: Rare earth elements are often added to chromium dioxide forming alloys to improve its high temperature oxidation resistance. The rare earths can be also added as oxide dispersions. Significant cost reductions are possible if rare earth oxide concentrates can be used instead of pure rare earth oxides, the former being the precursor to obtaining pure rare earth oxide. In this study the effect of adding pure and concentrates of rare earth oxides to AISI 304L on its oxidation behavior has been evaluated. AISI 304L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…(%)) of reactive elements, especially rare earths, to chromium dioxide forming alloys increased the oxidation resistance of these alloys by decreasing oxidation rates and by increasing oxide scale adhesion 1,2 . The rare earths have been: a) added as alloying elements or as oxide dispersions; b) implanted in the surface of the alloy; and c) applied as a coating on the surface of the alloy [3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…(%)) of reactive elements, especially rare earths, to chromium dioxide forming alloys increased the oxidation resistance of these alloys by decreasing oxidation rates and by increasing oxide scale adhesion 1,2 . The rare earths have been: a) added as alloying elements or as oxide dispersions; b) implanted in the surface of the alloy; and c) applied as a coating on the surface of the alloy [3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…The use of reactive elements, especially rare earths (RE) to improve high temperature oxidation resistance of chromium dioxide and alumina forming alloys is quite well documented. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The improvements are in the form of reduced oxidation rates and increased scale adhesion. The RE can be added to the alloy in elemental form or as oxide dispersions.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be applied as an oxide coating to the alloy surface. [3][4][5][6][7]15 Various mechanisms have been proposed to explain the effect of reactive elements in improving oxidation resistance and the most widely accepted mechanism attributes it to segregation of the reactive elements to the interface or to the oxide scale grain boundaries and blocking of Cr ion diffusion though the oxide scale [8][9][10][11] Studies carried out by Seo et al, about the effect of addition of Ce, La and Y to a Fe-22Cr-0.5Mn alloy on the oxidation behavior of the alloy at 800 °C, indicated that Y was the most effective element to reduce the growth rate of the oxide scale. 12 In recent years a number of studies have been carried out to exploit the benefits of rare earth additions on oxidation behavior of chromium dioxide and alumina forming alloys.…”
Section: Introductionmentioning
confidence: 99%
“…4 The addition of reactive elements such as yttrium, zirconium or cerium to these alloys improves the protective properties of surface oxides even more. [5][6][7][8][9] Rare earth oxides in the form of dispersions have also been added to these alloys to form protective surface oxides. 10 Implantations of lanthanum have been reported to increase the adhesion of the chromium dioxide layer, reduce its growth rate and increase conductivity.…”
Section: Introductionmentioning
confidence: 99%